Delving Beyond Conscious Attitudes: Validation of an Innovative Tool for Assessing Parental Implicit Attitudes Toward Physical Punishment. Issue 3 (10th January 2015) - Sturge‐Apple, Melissa L.; Rogge, Ronald D.; Peltz, Jack S.; Suor, Jennifer H.; Skibo, Michael A.; Lunkenheimer, Erika S.; Leerkes, Esther M.
<x xml:space="preserve">Abstract</x> Parenting scholars have long been interested in understanding the prevalence, determinants, and child outcomes associated with the use of physical discipline. To date, much of the empirical research in this area has utilized self‐report measures to assess this construct. However, the subjective nature of participants' explicit reports presents an important confound to studying this issue. Thus, the overarching aim of this study was to provide the first test of an implicit assessment of physical discipline through using a Go/No‐go Association Task (GNAT). A GNAT‐Physical Discipline was developed and examined in two separate studies of mothers and their 2–3‐year‐old child. One study was conducted in an online format and the second within a laboratory design. Across both studies, findings suggested that the GNAT‐Physical Discipline distinguished between positive and negative implicit attitudes towards the use of physical discipline. In addition, negative implicit attitudes were uniquely linked to maternal reports of physical discipline when compared to other discipline practices. Results suggest the potential for the GNAT paradigm in research on parental attitudes around the use of physical discipline in parenting contexts. In addition, our use of an online format (with implicit assessments of key constructs) demonstrates that child and family researchers may be able to explore their hypotheses in larger, geographically diverse samples. Copyright © 2015 John Wiley & Sons, Ltd.